Rola tlenowego rozkładu odpadów przed ich składowaniem w przebiegu procesów zachodzących na składowiskach = The influence of aerobic treatment of waste prior its storage on the processes occurring in landfill - Suchowska-Kisielewicz, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Currently, the most popular method of waste disposal is their deposition in landfills. Traditional landfills are characterized the high potential of pollutant emission causing long term risk to the environment and human health. These risks can be limited using the appropriate techniques of waste treatment prior it is landfilled. These risks can be limited using the appropriate techniques of waste treatment prior it is landfilled.
Keywords: odpady; rozkład tlenowy; odcieki; mechaniczno-biologiczne przetwarzanie odpadów; składowisko odpadów; wastes; aerobic degradation; leachate; mechanical-biological treatment; landfill